THE INFLUENCE OF DOCTOR'S COMMUNICATION SKILL AND PATIENT CHARACTERISTICS ON PATIENT COMPREHENSION OF CAESAREAN SECTION IN RSIA PURI BUNDA MALANG - Satiti, Yudha Rose; Hakim, Lukman; Rasyid, Harun Al (Jurnal Aplikasi Manajemen, 2017)
The new era of health culture is concerned about patient safety, where the patients have the right to obtain information from doctors about the actions & treatment for them. Preliminary study results show that comprehension level of Caesarean section patients is still low (56%) and there is a big risk for the hospital to get medical litigations. This study aims to determine the influence of physician communication skills and patient's characteristics against the patient's comprehension of caesarean section. This study was an observational study with the cross sectional approach with 70 post-cesarean patients samples using purposive sampling. Data were collected by a questionnaire containing questions about physician communication skills, patient's comprehension and patient's characteristics and this study using logistic regression analysis. The test results showed that simultaneously, there is significant influence between doctor's communication skills, age, a level of education and experience of the patient against the patient's comprehension. Partially, showed a significant influence of physician communication skills and patient experience on the patient's comprehension of a caesarean section, with the most dominant factor is physician communication skills.Therefore, the hospital can improve physician communication skills by doing communication training.